(untitled) (Journal of Information Systems and Technology Management, 2004)
This is an exploratory study of how Internet technologies are likely to have an impact on a specific industrial activity. Maintenance has long been the poor relation in industry despite being indispensable both in continuous process manufacturing and in discrete production. The research starts from the premise that maintenance has two key functions that can be related to management disciplines. These are the acquisition of spare parts, which is attached to purchasing and the deployment of technicians, engineers and subcontractor personnel which is jointly supervised by production, purchasing and human resource managers. The approach adopted was a review of current practices followed by a key informant study. Experts in several major industrial concerns were interviewed along with an opinion leader from a European maintenance federation were interviewed to analyse to what extent technology take-up is likely to affect both purchasing of spares and information management.